Chemistry and Characterization of Binary Organic Eutectics - Rai*, U.S.; Rai, R.N. (Asian Journal of Chemistry, 2010)
Phase diagrams of benzil with each of naphthalene, β-naphthol andp-chloronitrobenzene show the formation of simple eutectics. The growthvelocity (v) data studied at different undercoolings (ΔT) by measuring therate of movement of interface in a capillary obey the Hillig-Turnbullequation, v = u(ΔT)n, where u and n are constants depending on the natureof materials involved. Using enthalpy of fusion values, obtained by theDSC method, enthalpy of mixing, interfacial energy, entropy of fusion,excess thermodynamic functions and radius of the critical nucleus werecalculated. Microstructural investigations give characteristic features of theeutectics.